From plural society to Bangsa Malaysia : Ethnicity and nationalism in the politics of nation-building in Malaysia - Ishak, Mohamed Mustafa (1999)

(untitled)
The question of nation-building has always been a central issue in Malaysian politics. Whilst the country has been able to sustain a relatively stable politics since the 1969 tragedy, and hence spawn a rapid economic development (at least until the 1997 Asian economic crisis), the project of nation-building remained a basic national agenda yet to be fully resolved. This study investigates the delicate process of nation-building in Malaysia in the post 1970s, especially in the context of the vision of constructing the Bangsa Malaysia or 'a united Malaysian nation' enshrined in Mahathir's Vision 2020 project which was introduced in 1991. The aim of the study is firstly, to examine the underlying socio-political parameters that shaped and influenced the politics of nation-building in the country, and secondly, to explore the viability of the project of Bangsa Malaysia in the context of the daunting challenges involved in the process of nation-building. Drawing from a range of theoretical frameworks as well as from both primary and secondary data, the study contends that, based on the Malaysian experience, the potent interplay between the forces of ethnicity and nationalism constitute the crux of the problems in the politics of nation-building in Malaysia. This dialectic it is argued, stems from the prevalence of the varying perceptions of 'nation-of-intent' within and across ethnic groups. These phenomena have not only shaped the pattern of ethnic political mobilisation in the country, but above all, laid the most complex set of obstacles in the path of the project of nation-building. This study argues that the project of constructing the Bangsa Malaysia therefore, can be seen as a significant attempt by the state to reconcile the varying ethnic ideologies of nation-of-intent. It can also be considered as an attempt to consolidate Malay nationalism and cultural pluralism, thus, depicting 'the nation' as a 'mosaic of cultures', or reflecting a creation of 'a supra-ethnic' national identity. However, the viability of the envisaged project is yet to be tested. The concept itself is still vague to many people and the challenges ahead are enormous, involving political, economic, socio-cultural and religious issues. Indeed, the project risks becoming the 'latest' in the series of competing notions of nation-of-intent circulating in Malaysia. This study contends that whilst, to some extent, the socio-political landscape of Malaysian society has been rapidly changing, especially under the eighteen years of Mahathir's reign,ethnicity still pervades Malaysian political life. This study differs from many previous studies on nation-building in Malaysia which have mainly focused on either the historical dimensions or those which have examined the impact of key national policies. As such, it is hoped that this study would be able to provide an alternative perspective in the analysis of ethnic relations and nation-building in Malaysia, thus broadening the understanding of Malaysian politics and society.